The combination approach with Rhokinase inhibition and mechanical circulatory support in myocardial ischemia-reperfusion injury: Rho-kinase inhibition and ventricular unloading. (October 2022) - Miyahara, Shunsuke; Jenke, Alexander; Yazdanyar, Mariam; Kistner, Julia; Immohr, Moritz Benjamin; Sugimura, Yukiharu; Aubin, Hug; Kamiya, Hiroyuki; Okita, Yutaka; Lichtenberg, Artur; Akhyari, Payam
Background: It remains unclear whether the Rho-kinase (ROCK) inhibition in combination with mechanical circulatory support (MCS) had a synergic protective effect on myocardial ischemia (MI)/reperfusion injury in therapeutic strategies for acute myocardial infarction (AMI). We report the results of an approach using a rat model consisting of a miniaturized cardiopulmonary bypass (CPB) and AMI. Methods: A total of 25 male Wistar rats were randomized into 5 groups: (1) Sham: a suture was passed under the left anterior descending artery (LAD) creating no MI. A vehicle solution (0.9% saline) was injected intraperitoneally. (2) Myocardial ischemia (MI) + vehicle (MI + V): LAD was ligated for 30 min and reperfused for 120 min, followed by administration of vehicle solution. (3) MI + fasudil (MI + F): the work sequence of group 2, but the selective ROCK inhibitor fasudil (10 mg/kg) was administered instead. (4) MI + V + CPB: CPB was initiated 15 min after the ligation of the LAD to the end of the reperfusion, in addition to the work sequence in group 2. (5) In the MI + F + CPB group, the work sequence of group 4, but with fasudil administration (10 mg/kg). Results: Measurements of cardiac function through conductance catheter indicated that the drop of + dP/dt after reperfusion was moderately limited in MI + F + CPB (vs. MI + V, dP/dt p = 0.22). The preload recruitable stroke work was moderately improved in the MI + F + CPB ( p = 0.23) compared with the corresponding control animals (MI + V). Phosphorylated protein kinase B expression in the MI + V + CPB and MI + F + CPB was higher than that in MI + V ( p = 0.33). Conclusion: Therefore, fasudil administration with MCS resulted in a moderately better left ventricular performance.